Understanding the drivers of preferential migration of people living with HIV to fishing communities of Lake Victoria in Uganda - Sarah Nakamanya; Neema Nakyanjo; Caitlin Kennedy; William Ddaaki; Christine Ayanga; Richard John Ssemwanga; Jade Jackson; M. Kate Grabowski; Janet Seeley (Global Public Health, 2023)
Fishing communities around Lake Victoria have among the highest burdens of HIV globally. Growing evidence suggests that high HIV prevalence is partially due to selective migration of people living with HIV to fishing communities. However, the reasons for this preferential migration are unclear. We recruited 60 men and women for qualitative in-depth interviews (30% living with HIV; 70% recent migrants of unknown HIV status) from seven Ugandan fishing communities. Interviews discussed mobility histories and the social context surrounding migration. Interviews were audio-recorded, transcribed, and translated. A version of the ‘Push-Pull’ theory of migration helped structure a conceptual thematic framework for data analysis. Unfavourable conditions related primarily to stigma, social discrimination, humiliation, rejection or HIV labelling, and violence, induced individuals to leave their home communities. Factors which eventually resulted in migration to fishing communities included anticipating less HIV-related stigma and a safe, friendly environment that accommodates all people. Access to healthy food (fish) and the perceived availability of community-based HIV care services were also attractions. We found that stigma is the major social phenomenon shaping preferential migration to fishing communities in Uganda.